Genetic Diversity in FUB Genes of Fusarium oxysporum f. sp. cubense Suggests Horizontal Gene Transfer - Liu, Siwen; Wu, Bo; Lv, Shuxia; Shen, Zongzhuan; Li, Rong; Yi, Ganjun; Li, Chunyu; Guo, Xiuwu (Frontiers in Plant Science, 2019)
Fusaric acid (FA) is an important secondary metabolite of many Fusarium species and involved in the wilt symptoms caused in banana by Fusarium oxysporum f. sp. cubense (Foc). To investigate the evolution characteristics of the 12 Foc FA biosynthetic genes (FUB), coding sequences of the 12 FUB genes and 3 housekeeping genes, EF-1α/RPB1/RPB2 (translation elongation factor-1α/RNA polymerase II subunit I/RNA polymerase II subunit II), were subjected to genetic diversity analysis, phylogenetic analysis, recombination detection and selective pressure analysis. The results of selective pressure analysis showed that the 15 genes were mainly subjected to negative selection. However, significantly higher number of silent mutations, which could not be simply explained by selective pressure difference, was observed in the 12 FUB genes in Foc than in the three housekeeping genes. Infraspecies phylogeny and recombination detection analysis showed that significantly more horizontal gene transfer (HGT) events (normalized) had occurred in the FUB genes than in the three housekeeping genes. In addition, many of these events involved outgroup isolates and significantly increased the genetic diversity of FUB genes in Foc. The infraspecies phylogenetic analysis suggested that the polyphyletic phylogeny proposed for Foc requires further discussion, and the divergence of race 1, race 4 and the common ancestor of several Fusarium oxysporum (Fo) isolates pathogenic to nonbanana plants should have diverged over a short period. Finally, our results suggest that the FUB genes in Fo should have benefited from HGT to gain a relatively high genetic diversity to respond to different host plants and environments despite mainly being subject to negative selection.